Social learning processes in a citrus farming community of practice - Downsborough, Linda (Rhodes University, Faculty of Education, Department of Education, 2007)
Learning takes place in a number of ways. Situated learning for example, tries to shift the focus from the individual as a learner to the learner participating in the social world and from learning as a strictly cognitive process to a more encompassing view of social practice. The overall aim of this research was to gain a deeper understanding of the ways in which learning takes place in and between members of a citrus farming community, in other words it was to investigate the social learning processes. The research was undertaken in Patensie, a citrus farming community of the Gamtoos River Valley, Eastern Cape, South Africa. Data was generated through the use of interviews and informal discussions with participants together with document analysis, such as minutes of meetings. I also made observations of the learning interactions that were evident and also the interactions that were evident in the area as a whole. The data was analysed in two phases, the first involved reading across the interview transcripts and organizing the data under broad themes while the second phase made use of an analytical framework, a Community of Practice perspective to further analyze and engage with the data. I drew quite strongly on the ideas of situated learning, Communities of Practice and the notion of Legitimate Peripheral Participation (Lave & Wenger, 1991) as a means to understand, interpret and describe the social learning processes. The research highlighted that in this case study, citrus farmers learn in a number of sociological ways, for example through intergenerational learning (in the family), learning from each other in a Community of Practice, learning from private consultants and extensions officers as well as from other organizations and institutions. It also considered how farmers' learning had influenced land use practice in the area. This brought to the fore an emerging partnership with a conservation agent based on providing economic incentives to farmers to engage in sustainable landuse practices. It is hoped that this research may inform future educational endeavours by shedding light on the social learning processes and by drawing attention to key aspects of learning that may previously have been overlooked in research.
Keywords: Uncatalogued